Identification of clustered YY1 binding sites in imprinting control regions - Do Kim, Jeong; Hinz, Angela K.; Bergmann, Anne; Huang, Jennifer M.; Ovcharenko, Ivan; Stubbs, Lisa; Kim, Joomyeong (Genome Research, 2006)
Mammalian genomic imprinting is regulated by imprinting control regions (ICRs) that are usually associated with tandem arrays of transcription factor binding sites. In this study, the sequence features derived from a tandem array of YY1 binding sites of Peg3-DMR (differentially methylated region) led us to identify three additional clustered YY1 binding sites, which are also localized within the DMRs of Xist, Tsix, and Nespas. These regions have been shown to play a critical role as ICRs for the regulation of surrounding genes. These ICRs have maintained a tandem array of YY1 binding sites during mammalian evolution. The in vivo binding of YY1 to these regions is allele specific and only to the unmethylated active alleles. Promoter/enhancer assays suggest that a tandem array of YY1 binding sites function as a potential orientation-dependent enhancer. Insulator assays revealed that the enhancer-blocking activity is detected only in the YY1 binding sites of Peg3-DMR but not in the YY1 binding sites of other DMRs. Overall, our identification of three additional clustered YY1 binding sites in imprinted domains suggests a significant role for YY1 in mammalian genomic imprinting.